RPL19 Is a Prognostic Biomarker and Promotes Tumor Progression in Hepatocellular Carcinoma - Rao, Benchen; Li, Jianhao; Ren, Tong; Yang, Jing; Zhang, Guizhen; Liu, Liwen; Wang, Haiyu; Huang, Maoxin; Ren, Zhigang; Yu, Zujiang (Frontiers in Cell and Developmental Biology, 2021)
Abstract Background: Hepatocellular carcinoma (HCC) is one of the most common malignancies, and the therapeutic outcome remains undesirable due to its recurrence and metastasis. Gene dysregulation plays a pivotal role in the occurrence and progression of cancer, and the molecular mechanisms are largely unknown. Methods: The differentially expressed genes of HCC screened from the GSE39791 dataset were used to conduct weighted gene coexpression network analysis. The selected hub genes were validated in The Cancer Genome Atlas database and 11 HCC datasets from the Gene Expression Omnibus database. Then, a tissue microarray comprising 90 HCC specimens and 90 adjacent normal specimens was used to validate the hub genes. Moreover, the Hallmark, Gene Ontology and Kyoto Encyclopedia of Genes and Genomes databases were used to identify enriched pathways. Then, we conducted the immune infiltration analysis. Results: A total of 17 coexpression modules were obtained by weighted gene coexpression network analysis. The green, blue and purple modules were the most relevant to HCC samples. Four hub genes, RPL19, RPL35A, RPL27A and RPS12, were identified. Interestingly, we found that all four genes were highly expressed in HCC and that their high expression was related to a poor prognosis by analyzing the The Cancer Genome Atlas and Gene Expression Omnibus databases. Furthermore, we investigated RPL19 in HCC tissue microarrays and demonstrated that RPL19 was overexpressed in tumor tissues compared with nontumor tissues(p=0.016). Moreover, overexpression of RPL19 predicted a poor prognosis in hepatocellular carcinoma (p<0.0007). Then, enrichment analysis revealed that cell cycle pathways were significantly enriched, and bile acid metabolism-related pathways were significantly down-regulated when RPL19 was highly expressed. Furthermore, immune infiltration analysis showed that immune response was suppressed. Conclusions: Our study demonstrates that RPL19 may play an important role in promoting tumor progression and is correlated with a poor prognosis in HCC. RPL19 may serve as a promising biomarker and therapeutic target for the precise diagnosis and treatment of HCC in the future.